A Review of Value Added Tax Policy on Animal Feed Industry in Indonesia - Raymundus, Torganda; Rosdiana, Haula (UI Scholars Hub, 2021)
The role of tax policy is very important in efforts to increase business productivity, particularly through the provision of tax incentives in line with one of the principles in supply-side tax policy. However, studies to evaluate the Value Added Tax (VAT) policy implementation on animal feed using the supply-side tax policy perspective is very rare. This research is aimed at analyzing the impact of VAT incentives on animal feeds on the tax burden borne by the taxpayer both in carrying out their obligations and obtaining their rights or so called cost of taxation in Indonesia. The research uses qualitative approach with both qualitative and quantitative data. The data is collected through in-depth interview with eleven relevant informants, literature study, and secondary data. The study finds that (1) the policy raises the cost of taxation in the form of compliance cost, direct money cost, time cost and psychological cost for the animal feed industry, (2) the policy has a contra-productive effect to the effort of improving the national animal feed production capacity along with the cascading effect and opportunity cost arising from the policy implementation; and (3) the policy warrants a different impact for domestic animal feed producers and importers due to to the absence of the cascading effect. These findings highlight that the application of tax-incentive distribution of VAT on animal feed input materials disrupts the company’s cash flow and limits the production capacity for business actors since it is in contradiction to the supply-side tax policy principle. This study recommendsa re-regulation and de-regulation as an alternative to tackle the issues.